2012
DOI: 10.1016/j.jtbi.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Prosperity is associated with instability in dynamical networks

Abstract: Social, biological and economic networks grow and decline with occasional fragmentation and re-formation, often explained in terms of external perturbations. We show that these phenomena can be a direct consequence of simple imitation and internal conflicts between ‘cooperators’ and ‘defectors’. We employ a game-theoretic model of dynamic network formation where successful individuals are more likely to be imitated by newcomers who adopt their strategies and copy their social network. We find that, despite usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 60 publications
7
66
0
Order By: Relevance
“…For example, when interactions are spatial, then individuals' choices to relocate would determine evolving assortativity through dynamical networks. Importantly, we note that dynamical networks may lead to the re-scaling of payoffs, as reported by Pacheco et al (2006a,b), to instability, as reported by Cavaliere et al (2012), as well as to the emergence of multilevel selection and strong heterogeneities, as reported by Szolnoki and Perc (2009) and Szolnoki et al (2008). This surely has implications for local assortativity and voting procedures (which may no longer be global) and is an interesting aspect that deserves attention in future research.…”
Section: Discussionsupporting
confidence: 66%
“…For example, when interactions are spatial, then individuals' choices to relocate would determine evolving assortativity through dynamical networks. Importantly, we note that dynamical networks may lead to the re-scaling of payoffs, as reported by Pacheco et al (2006a,b), to instability, as reported by Cavaliere et al (2012), as well as to the emergence of multilevel selection and strong heterogeneities, as reported by Szolnoki and Perc (2009) and Szolnoki et al (2008). This surely has implications for local assortativity and voting procedures (which may no longer be global) and is an interesting aspect that deserves attention in future research.…”
Section: Discussionsupporting
confidence: 66%
“…If you end or do not begin an interaction, because a player has defected against someone else, then this is a form of indirect reciprocity (Fu et al, 2008). Likewise it is a form of indirect reciprocity if you preferentially seek interactions with people who have cooperated with others (Tarnita et al, 2009;Du and Fu, 2011;Cavaliere et al, 2012). Optional interactions and ostracism have also been discussed in the context of multi-player games such as the public goods game or common pool resource games (Aktipis, 2004;Chiang, 2008;Nakamura and Masuda, 2012;Tavoni et al, 2012;Lade et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3. This kind of highly cooperative, but unstable dynamic is often witnessed in the evolution of cooperation literature [22,36].…”
Section: Modelmentioning
confidence: 98%